BOSHLANG‘ICH SINF O‘QUVCHILARINING KREATIVLIGINI RIVOJLANTIRISHDA XALQ OG‘ZAKI IJODINING AHAMIYATI - Dauletmuratova, B.M. (SCIENCE and SOCIETY, 2025)
This article discusses the importance and effectiveness of developing creative thinking abilities in primary school students based on musical folklore, one of the examples of folk art. Creativity as an indicator of creative development, its essence is considered alternatively, from the point of view of the characteristics of the perceptual, cognitive and emotional spheres of the individual. Creativity is defined as a set of mental and personal characteristics of a person aimed at solving problems in a non-standard way and creating unusual ideas.